2019
DOI: 10.1111/1541-4337.12506
|View full text |Cite
|
Sign up to set email alerts
|

Sorghum Grain: From Genotype, Nutrition, and Phenolic Profile to Its Health Benefits and Food Applications

Abstract: Globally, sorghum is one of the most important but least utilized staple crops. Sorghum grain is a rich source of nutrients and health‐beneficial phenolic compounds. The phenolic profile of sorghum is exceptionally unique and more abundant and diverse than other common cereal grains. The phenolic compounds in sorghum are mainly composed of phenolic acids, 3‐deoxyanthocyanidins, and condensed tannins. Studies have shown that sorghum phenolic compounds have potent antioxidant activity in vitro, and consumption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
175
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(185 citation statements)
references
References 164 publications
(318 reference statements)
3
175
0
7
Order By: Relevance
“…Sorghum ( Sorghum bicolor (L.) Moench), the fifth primary cereal crop in the world, has been attracting much attention because of its high content of phytochemicals (Ragaee, Abdel‐Aal, & Noaman, 2006). Sorghum grains contain high portion of bioactive phytochemicals such as phenolic acids, procyanidins, 3‐deoxyanthocyanidins, and condensed tannins (Vanamala, Massey, Pinnamaneni, Reddivari, & Reardon, 2017; Xiong, Zhang, Warner, & Fang, 2019a). Epidemiological studies have consistently shown that the consumption of sorghum products is associated with reduced risk of chronic diseases, including type II diabetes, cardiovascular diseases, and cancer owing to the phenolic profile (Awika & Rooney, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Sorghum ( Sorghum bicolor (L.) Moench), the fifth primary cereal crop in the world, has been attracting much attention because of its high content of phytochemicals (Ragaee, Abdel‐Aal, & Noaman, 2006). Sorghum grains contain high portion of bioactive phytochemicals such as phenolic acids, procyanidins, 3‐deoxyanthocyanidins, and condensed tannins (Vanamala, Massey, Pinnamaneni, Reddivari, & Reardon, 2017; Xiong, Zhang, Warner, & Fang, 2019a). Epidemiological studies have consistently shown that the consumption of sorghum products is associated with reduced risk of chronic diseases, including type II diabetes, cardiovascular diseases, and cancer owing to the phenolic profile (Awika & Rooney, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, consumers nowadays are interested in indigenous crops, like sorghum, that offer health benefits and gluten‐free advantage. Compared to maize, sorghum is known to contain polyphenol compounds such as gallic acid, caffeic acid, naringenin, eriodictyol, apigenin, luteolin, and 3‐deoxyanthocyanidins (Xiong, Zhang, Warner, & Fang, 2019). These compounds have unique bioactive properties such as cancer prevention, promotion of cardiovascular health and reduction of chronic inflammation, and oxidative stress (Yang, Allred, Dykes, Allred, & Awika, 2015; Yang, Allred, Geera, Allred, & Awika, 2012; Yang, Browning, & Awika, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Tortilla chips made entirely from white sorghum showed the darkest color. The increase of white sorghum in tortilla chips was associated with the reduction of a yellow coloration and an increase in red tones in products, which might be related to the higher concentration of tannins in tortilla chips(Sedghi, Golian, Soleimani‐Roodi, Ahmadi & Aami‐Azghadi, 2012; Xiong, Zhang, Warner, & Fang, 2019), as it can be seen in Table 1. The presence of red tones on the surface of the samples could be also explained by the contribution of brown‐colored compounds generated during the frying operation, which leads to the reaction between amino acids and sugars present in the flour of sorghum and corn by the effect of the Maillard reaction (Tamanna & Mahmood 2015; Wong, Aziz, & Mohamed, 2008).…”
Section: Resultsmentioning
confidence: 95%
“…The phenolic compounds present in grains are mostly bound to cell wall structures and a proportion of them are lost during the nixtamalization process (Delgado et al., 2016). The presence of several phenolic compounds with anti‐proliferative effects on cancer cells has been reported in sorghum grains (Cox et al., 2019), and are mainly comprised of phenolic acids, flavonoids, and condensed tannins (Shen et al., 2018; Xiong et al., 2019). It has been reported that Total Phenolic Content (TPC) is highly affected by the color of sorghum (Shen et al., 2018) and corn grains (Delgado et al., 2016) as well as the different varieties and conditions of agricultural production (Guzmán‐Maldonado, Vázquez‐Carrillo, Aguirre‐Gómez, & Serrano‐Fujarte, 2015; Wu, Johnson, Bornman, Bennett, & Fang, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation